The professional responsibility of doctors and psychiatrists in mental health protection - Fiori, Angelo (Medicina e Morale, 2024)
The history of madness is neither the history of medicine nor that of psychiatry but, to some extent, a non-marginal part of the history of mankind and its societies as they have changed over time, albeit Vichiana-like, with recurring and permanent motifs.